Diagnostic value of 3DFLAIR in clinical practice for the detection of infratentorial lesions in multiple sclerosis in regard to dual echo T2 sequences. Issue 102 (May 2018) - Hannoun, Salem; Heidelberg, Damien; Hourani, Roula; Nguyen, Thi Thuy Trang; Brisset, Jean-Christophe; Grand, Sylvie; Kremer, Stéphane; Bonneville, Fabrice; Guttmann, Charles R.G.; Dousset, Vincent; Cotton, François
Highlights: 3DFLAIR was proved to be more sensitive in detecting infratentorial lesions than 2DT2/PD. The more the radiologist is specialized and experienced, the more his sensibility to detect lesions is optimized. Lesion detection accuracy is important in MS follow-up that takes into account new lesions number to adapt patients' treatment. Abstract: Background and purpose: The aim of this prospective study is to investigate and evaluate in clinical practice the diagnostic impact of 3DFLAIR in regards to 2DT2/PD in terms of infratentorial lesions detection in multiple sclerosis (MS). Material and methods: 164 MS patients from the OFSEP database were reviewed retrospectively. MR examinations were performed on 1.5T or 3T systems from four different centers. Infratentorial lesions were counted and allocated to different regions of the posterior fossa by three raters independently (junior resident, resident with an expertise in neuroradiology, and senior neuro-radiologist) on the 3DFLAIR and 2DT2/PD. Both sequences do not have the same spatial resolution but reflect what is recommended by most of the consensus and done in clinical practice. Results: With an overall number of 528 for Rater-1 and 798 for Rater-2 infratentorial lesions, 3DFLAIR had a significantly higher number of lesions detected than 2DT2/PD (303 for Rater-1 and 370 for Rater-2). The prevalence of trigeminal lesions detected by using 3DFLAIR was also significantly higher than 2DT2/PD. ROC analysis showed 3DFLAIR to be more specific and sensitive than 2DT2/PD. An overall difference between all three Raters has been observed. The more the Rater is experienced the more lesions he detects. Conclusion: Along with the radiologist ability to detect lesions based on his level of experience, the OFSEP optimized 3DFLAIR can significantly improve infratentorial lesion detection in MS compared to 2DT2/PD. This is important in MS follow-up that takes into account new lesions number to adapt patients' treatment.